Strontium(II) and mechanical loading additively augment bone formation in calcium phosphate scaffolds. Issue 1 (26th June 2017) - Reitmaier, Sandra; Kovtun, Anna; Schuelke, Julian; Kanter, Britta; Lemm, Madlin; Hoess, Andreas; Heinemann, Sascha; Nies, Berthold; Ignatius, Anita
ABSTRACT: Calcium phosphate cements (CPCs) are widely used for bone‐defect treatment. Current developments comprise the fabrication of porous scaffolds by three‐dimensional plotting and doting using biologically active substances, such as strontium. Strontium is known to increase osteoblast activity and simultaneously to decrease osteoclast resorption. This study investigated the short‐ and long‐term in vivo performances of strontium(II)‐doted CPC (SrCPC) scaffolds compared to non‐doted CPC scaffolds after implantation in unloaded or load‐bearing trabecular bone defects in sheep. After 6 weeks, both CPC and SrCPC scaffolds exhibited good biocompatibility and osseointegration. Fluorochrome labeling revealed that both scaffolds were penetrated by newly formed bone already after 4 weeks. Neither strontium doting nor mechanical loading significantly influenced early bone formation. In contrast, after 6 months, bone formation was significantly enhanced in SrCPC compared to CPC scaffolds. Energy dispersive X‐ray analysis demonstrated the release of strontium from the SrCPC into the bone. Strontium addition did not significantly influence material resorption or osteoclast formation. Mechanical loading significantly stimulated bone formation in both CPC and SrCPC scaffolds after 6 months without impairing scaffold integrity. The most bone was found in SrCPC scaffolds under load‐bearing conditions. Concluding, these results demonstrate that strontium doting and mechanical loading additively stimulated bone formation in CPC scaffolds and that the scaffolds exhibited mechanical stability under moderate load, implying good clinical suitability. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:106–117, 2018. Abstract : 3D‐printed porous scaffolds fabricated on the basis of an injectable ready‐to‐use CPC paste exhibited excellent biocompatibility and osseointegration in critical size bone defects in sheep. Furthermore, the scaffolds exhibited sufficient mechanical stability after implantation under moderately load‐bearing conditions. Strontium doting resulted in improved and sustained bone formation in the scaffolds, which may be advantageous compared to growth factors with limited biological half‐life. These results implicate that the scaffolds might be suitable for clinical application, particularly in osteoporotic bone.